2017
DOI: 10.3346/jkms.2017.32.11.1749
|View full text |Cite
|
Sign up to set email alerts
|

Researcher and Author Profiles: Opportunities, Advantages, and Limitations

Abstract: Currently available online profiling platforms offer various services for researchers and authors. Opening an individual account and filling it with scholarly contents increase visibility of research output and boost its impact. This article overviews some of the widely used and emerging profiling platforms, highlighting their tools for sharing scholarly items, crediting individuals, and facilitating networking. Global bibliographic databases and search platforms, such as Scopus, Web of Science, PubMed, and Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 62 publications
0
34
0
7
Order By: Relevance
“…More recently, Gasparyan et al (2017) have provided a useful overview of both the widely used and emerging online profiling platforms, some of which are provided as a service by an ASNS. They have concluded that "Opening an individual account and filling it with scholarly contents increase visibility of research output and boost its impact" (p. 1749).…”
Section: Online Profiling Platformsmentioning
confidence: 99%
“…More recently, Gasparyan et al (2017) have provided a useful overview of both the widely used and emerging online profiling platforms, some of which are provided as a service by an ASNS. They have concluded that "Opening an individual account and filling it with scholarly contents increase visibility of research output and boost its impact" (p. 1749).…”
Section: Online Profiling Platformsmentioning
confidence: 99%
“…The interface allows the user to input structured citation lists that may constitute an online curriculum vitae, including an ORCID identifier, an NCBI My Bibliography link, or the public uniform resource locator (URL) of a Zotero personal library or group [50][51][52]. This selection was informed both by prevalence of use [53][54][55] and by the provision of citation information via structured formats that can be parsed for comparisons to journals in SPI-Hub. Once journal matches are identified, the tool returns a list of hyperlinks to SPI-Hub records (supplemental Appendix D).…”
Section: Spi-hub: Scholarly Publishing Information Hub™ Featuresmentioning
confidence: 99%
“…Instead, requiring authors and reviewers to declare and link a universal researcher identification such as the Open Researcher and Contributor Identifier (ORCID) may also help prove the veracity of the identity of such scientists. 33 43 Also, the use of reviewer lists from voluntary databases such as Publons, where many reviewers register profiles as well as many other journals directly upload peer reviewer names with their permission (with or without peer review reports depending on the journal policies), may increase the likelihood of identifying authentic peer reviewers, or verifying the identity of suggested peer reviewers. 44 Similar initiatives should be promoted by peer reviewers and editors together in the future.…”
Section: Peer Review Practicesmentioning
confidence: 99%